Improving Web Search Results Using KWSSWS System (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In today's digital age, efficient web searching and PDF retrieval have become crucial for various applications and industries. Development Operations (DevOps) plays a vital role in enhancing web search capabilities and streamlining PDF retrieval processes. This research paper explores the implementation of the Keyword Search System on Web Searching (KWSSWS) on Google PDFs retrieval to improve both DevOps and web searching for PDF documents. The study investigates the effectiveness of the (KWSSWS) system in enhancing the search experience and the performance of DevOps processes. The research methodology involves an experimental design and data analysis to evaluate the system's performance using real-world data. The results demonstrate the potential of the (KWSSWS) system to enhance web searching and PDF retrieval, thus providing valuable insights for further advancements in this domain. The advantage of the proposed (KWSSWS) system is that the collected files are very accurate and match the entered keywords hundred percent. This system is very useful primarily for all researchers around the world in various disciplines, where consider time and quality as the most important factors.